Age-related Change of Hearing Acuity in High Frequencies in Diabetics and Non-diabetics - Terunuma, Tsumoru; Kusakari, Jun; Komeno, Masae; Wada, Tetsuro; Yoshie, Haruei; Ito, Zenya; Tachihara, Narihisa; Ase, Yuji (AUDIOLOGY JAPAN, 1996)
Hearing acuity of diabetics and non-diabetics was measured using a standard pure tone audiometer and high frequency audiometer, which can generate high-pitched tones up to 18kHz. All of the subjects in this study had normal ear drum and no complaints including tinnitus and vertigo. The standard pure tone audiometry revealed a gradual threshold elevation up to the sixties and faster elevation in the older generations. The hearing thresholds at the frequencies above 8kHz were found to start to evidently elevate even in the thirties. The constant threshold elevation seemed to continue until the seventies, in which the ears can hardly hear the sounds of 100dB SPL at these frequencies. On the other hand, comparison between the diabetics and non-diabetics suggested that hearing levels at the frequencies between 1kHz and 8kHz of the standard pure tone audiometry could be better parameters than the high frequency audiometry to detect hearing impairment in diabetics.